Identification, characterization, and overexpression of a phytase with potential industrial interest - Shi, X.; Sun, M.; Zhou, B.; Wang, X.
A high phytase-producing strain of Aspergillus niger N-3 was identified by screening 104 microbial strains. The gene for A. niger N-3 was cloned and expressed in Pichia pastoris. The coding region without the introns and putative signal sequence was comprised of 1347 nucleotides. It encoded a polypeptide of 448 amino acids, exhibiting high amino acid sequence homologies (94.87
Keywords: PHYTASE; STRAIN SCREENING; OVEREXPRESSION; ENZYMATIC PROPERTIES; GLYCOSYLATION